Transformative Social Emotional Learning: Bridging the Gap Between Teacher Preparation and Student Learning - (:unkn) unknown (My University, 2022)
The purpose of this qualitative research study was to explore the practices and perceptions of educators implementing a schoolwide SEL curriculum. This study sought to identify aspects that promote and prevent effective SEL programming in schools by answering the following questions: How do educators implement SEL curriculum in a diverse school setting? How do educators’ understandings and beliefs about SEL impact schoolwide program implementation? and What transformative qualities of educators’ knowledge and practices emerge in the examination of their beliefs about SEL? The data for this study was collected through a survey and semi-structured interview with three participants. Three key findings emerged: a) the lived experiences and perceptions of competencies impact educators’ approach to program implementation, b) limitations within the structure of the curriculum and educators’ workarounds also impacted implementation, and c) classroom practices grounded in SEL demonstrated the potential to create transformative experiences and spaces.
Keywords: Social Emotional Learning; Transformative SEL